The role of Spartina maritima and Sarcocornia fruticosa on trace metals retention in Ria Formosa, Portugal - Moreira, Manuela M. (2013)
Over the last years, phytoremediation has become an increasingly recognized pathway for contaminant removal from water and shallow soils. Assessing the phytoremediation potential of wetlands is complex due to variable conditions of hydrology, soil/sediment types, plant species diversity, growing season and water chemistry. Physico-chemical properties of wetlands provide many positive attributes for remediating contaminants. Saltmarsh plants can sequestrate and inherently tolerate high metal concentrations found in saltmarsh sediments.